White and Gray Matter Abnormalities in Australian Footballers With a History of Sports-Related Concussion: An MRI Study. (19th June 2021) - Major, Brendan; Symons, Georgia F; Sinclair, Ben; O'Brien, William T; Costello, Daniel; Wright, David K; Clough, Meaghan; Mutimer, Steven; Sun, Mujun; Yamakawa, Glenn R; Brady, Rhys D; O'Sullivan, Michael J; et al.
Abstract: Sports-related concussion (SRC) is a form of mild traumatic brain injury that has been linked to long-term neurological abnormalities. Australian rules football is a collision sport with wide national participation and is growing in popularity worldwide. However, the chronic neurological consequences of SRC in Australian footballers remain poorly understood. This study investigated the presence of brain abnormalities in Australian footballers with a history of sports-related concussion (HoC) using multimodal MRI. Male Australian footballers with HoC ( n = 26), as well as noncollision sport athletes with no HoC ( n = 27), were recruited to the study. None of the footballers had sustained a concussion in the preceding 6 months, and all players were asymptomatic. Data were acquired using a 3T MRI scanner. White matter integrity was assessed using diffusion tensor imaging. Cortical thickness, subcortical volumes, and cavum septum pellucidum (CSP) were analyzed using structural MRI. Australian footballers had evidence of widespread microstructural white matter damage and cortical thinning. No significant differences were found regarding subcortical volumes or CSP. These novel findings provide evidence of persisting white and gray matter abnormalities in Australian footballers with HoC, and raise concerns related to the long-term neurological health of these athletes.